Protocol on the Improvement of the Humanitarian Situation in Darfur (Tufts Archival Research Center, 2005)
Protocol between the Government of the Sudan (GoS), the Sudan Liberation Movement/Army (SLM/A) and the Justice and Equality Movement (JEM) on the Improvement of the Humanitarian Situation in Darfur. Includes signatures.